128k views
4 votes
Which expression is equivalent to the given question?

(10c^6d^-5)(2c^-5d^4)

A. 20c/d

B. 20cd

C. 20/c^30d^20

D. 20c^30d^20

2 Answers

1 vote

Answer:

20c/d

Explanation:

User Ninsau
by
4.8k points
7 votes

Answer:


(10c^6d^(-5))* (2c^(-5)d^4)=
(20c)/(d)

Explanation:

The given expression is :


(10c^6d^(-5))* (2c^(-5)d^4)

We need to find the equivalent expression for the given expression

We know that,
x^ax^b=x^(a+b)


c^6c^(-5)=c^(6-5)=c\\\\d^(-5)d^4=d^(-5+4)=(1)/(d)

So,


(10c^6d^(-5))* (2c^(-5)d^4)=20* c* (1)/(d)\\\\=(20c)/(d)

Hence, the correct option is (a) i.e.
(20c)/(d).